(untitled) - Purdom, Collin E. (London, 1993)
Genetics and Fish Breeding provides a thorough review of this important subject, highlighting species which are bred commercially, such as salmon, trout, carp and goldfish. The author, who is an acknowledged expert in this subject, has drawn together a wealth of information, providing a book which should be bought by all fish biologists, fisheries scientists, geneticists and aquarists.
Keywords: Fishes,Fishes; Breeding,Genetics